Impaired Immune Response to SARS-CoV-2 Vaccination in Dialysis Patients and in Kidney Transplant Recipients. Issue 9 (30th September 2021) - Kolb, Thilo; Fischer, Svenja; Müller, Lisa; Lübke, Nadine; Hillebrandt, Jonas; Andrée, Marcel; Schmitz, Michael; Schmidt, Claudia; Küçükköylü, Seher; Koster, Lynn; Kittel, Margarethe; Weiland, Lea; et al.
Visual Abstract: Abstract : Key Points: Immune response to the coronavirus disease 2019 vaccination is significantly reduced in patients with kidney failure compared with controls without kidney failure. After two vaccinations, kidney transplant recipients show the lowest levels of IgGs specific to severe acute respiratory syndrome coronavirus 2, with the lowest neutralizing capacity. These data suggest that vaccination strategies need modification in kidney transplant recipients and patients on dialysis. Background: Patients with kidney failure on dialysis or after renal transplantation have a high risk for severe COVID-19 infection, and vaccination against SARS-CoV-2 is the only expedient prophylaxis. Generally, immune responses are attenuated in patients with kidney failure, however, systematic analyses of immune responses to SARS-CoV-2 vaccination in patients on dialysis and in kidney transplant recipients (KTRs) are still needed. Methods: In this prospective, multicentric cohort study, antibody responses to COVID-19 mRNA vaccines (BNT162b2 [BioNTech/Pfizer] or mRNA-1273 [Moderna]) were measured in 32 patients on dialysis and in 28 KTRs. SARS-CoV-2–specific antibodies and neutralization capacity were evaluated and compared with controls ( n =78) of a similar age range. Results: After the first vaccination, SARS-CoV-2–specific antibodies were nearly undetectable in patients with kidney failure. After the second vaccination, 93% of the controls and 88% of patients on dialysis but only 37% of KTRs developed SARS-CoV-2–specific IgG above cutoff. Moreover, mean IgG levels were significantly lower in KTRs (54±93 BAU/ml) compared with patients on dialysis (503±481 BAU/ml; P <0.01). Both KTRs and patients on dialysis had significantly lower IgG levels compared with controls (1992±2485 BAU/ml; P <0.001 and P <0.01, respectively). Importantly, compared with controls, neutralizing antibody titers were significantly lower in KTRs and patients on dialysis. After the second vaccination, 76% of KTRs did not show any neutralization capacity against SARS-CoV-2, suggesting impaired seroprotection. Conclusions: Patients with kidney failure show a significantly weaker antibody response compared with controls. Most strikingly, only one out of four KTRs developed neutralizing antibodies against SARS-CoV-2 after two doses of vaccine. These data suggest that vaccination strategies need modification in KTRs and patients on dialysis. Clinical Trial registry name and registration number: Vaccination Against COVID-19 in Chronic Kidney Disease, NCT04743947